2007
DOI: 10.1086/513200
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Hepatitis B Surface Antigen (HBsAg) and Heterologous Subtype-Specific Antibodies to HBsAg among Patients with Chronic Hepatitis B Virus Infection

Abstract: HBsAg and anti-HBs with an unmatched specificity coexisted in 4.9% of patients. The presence of anti-HBs was not associated with the appearance of specific HBV mutants in patients with chronic infection. Apparently, the presence of anti-HBs in patients with chronic HBV infection did not lead to a selection of HBV escape mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
112
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 20 publications
15
112
5
Order By: Relevance
“…This ratio is lower than the 8.9% reported by Lada et al [2006], but is close to the 4.9% of 411 chronic hepatitis B virus carriers investigated in China [Zhang et al, 2007], suggesting possible demographic or geographical variability in these statistical differences. The mechanism of the coexistence of HBsAg and anti-HBs is still not entirely clear, but one explanation might be the selection of the immune escape mutant.…”
Section: Discussioncontrasting
confidence: 47%
“…This ratio is lower than the 8.9% reported by Lada et al [2006], but is close to the 4.9% of 411 chronic hepatitis B virus carriers investigated in China [Zhang et al, 2007], suggesting possible demographic or geographical variability in these statistical differences. The mechanism of the coexistence of HBsAg and anti-HBs is still not entirely clear, but one explanation might be the selection of the immune escape mutant.…”
Section: Discussioncontrasting
confidence: 47%
“…Therefore, routine screening for HBV in schizophrenia patients is advocated, and HBV as well as hepatitis A immunization is recommended. In this study, 38.1% of HBsAg-positive patients showed coexistence of HBsAb, which was significantly higher than previously reported results of 3%-10% [22][23][24][25][26]. The coexistence of HBsAg and antiHBs was regarded simply as superinfection with a different subtype of HBV [27].…”
Section: Discussioncontrasting
confidence: 62%
“…The coexistence of HBsAg and antiHBs was regarded simply as superinfection with a different subtype of HBV [27]. Some studies have suggested that the coexistence of HBsAg and HBsAb is associated with high replicative activity of HBV and mutations in the viral surface gene, which may alter the antigenicity of HBsAg and lead to subsequent failure of HBsAb neutralization [22,23,28]. Additionally, some studies reported that coexistence of HBsAg and HBsAb could be detected in immunosuppressive patients with organ transplantation, HIV infection, and prolonged corticosteroid therapy [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Though the step of reverse transcription from pregenomic RNA to the minus DNA strand by HBV polymerase may produce a large number of viral variants, only the variants with selective advantages would grow. It is interesting that substitutions at aa residue 126 of HBsAg occurred frequently in patients with chronic HBV infection [42] . At least 5 different residues were found at aa position 126: I, T, S, A and, less frequently, N [33,35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…PCR was performed over 30 cycles, with 1 min at 94 ° , 1 min at 50 ° and 2 min at 72 ° . Sequence analysis was performed directly with PCR products, using the primers 6DC 5 -GCACACGGAATTCCGAGGACTGGGGAC C-CTG-3 (nt 131-148) and S7D 5 -GACACCAAGCTTGGTTAGG-GTTTAAATGTATACC-3 (nt 845-825) [42] .…”
Section: Amplification and Sequence Analysis Of S Genementioning
confidence: 99%